1999
DOI: 10.1046/j.1432-1327.1999.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the 17‐kDa peptide‐binding domain of the molecular chaperone HSC70

Abstract: Crystallographic and biochemical studies have indicated that the peptide-binding site of the molecular chaperone HSC70 is located in a small subdomain comprising a b-sheet motif followed by a helical region, and there is some evidence of the involvement of this site in oligomerization of the protein.To determine the structure of this subdomain in solution and examine its involvement in oligomerization of HSC70, a 17-kDa protein (residues 385±540 of HSC70) consisting mainly of the peptide-binding site was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
4
33
1
Order By: Relevance
“…The 10-kDa C-terminal lid sub-domain (amino acids 542-646) of rat Hsc70, which forms an elongated bundle-like structure, dictates the self-association (22). In contrast, Fouchaq et al (20) reported that the 17-kDa peptide-binding sub-domain (amino acids 385-540 of Hsc70) was involved in the oligomerization process. The results obtained in the present study do not accord with either of these reports.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The 10-kDa C-terminal lid sub-domain (amino acids 542-646) of rat Hsc70, which forms an elongated bundle-like structure, dictates the self-association (22). In contrast, Fouchaq et al (20) reported that the 17-kDa peptide-binding sub-domain (amino acids 385-540 of Hsc70) was involved in the oligomerization process. The results obtained in the present study do not accord with either of these reports.…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence that the 30-kDa C-terminal client-binding domain is responsible for the dimerization of 70-kDa heat shock cognate protein Hsc70 (19,20). It has been reported that the 30-kDa C-terminal domain can be divided into N-terminal 18-kDa and C-terminal 10-kDa sub-domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TKD sequence, which is exposed to the extracellular milieu of tumors, resides in the C-terminally localized oligomerization domain of the Hsp70 molecule (11). Furthermore, this TKD peptide in combination with low-dose IL-2 has been found to stimulate the migratory and cytolytic activity of NK cells against membrane Hsp70 + tumor cells (12).…”
mentioning
confidence: 99%
“…ATP binding to the Nterminal domain induces a global conformational change in DnaK (7) which is thought to displace the lid from the top of the ␤-sandwich subdomain, creating the low affinity form of the protein. To gain insight into the function of the lid, slightly different lidless forms of DnaK and eukaryotic Hsp70s have been engineered (9,(15)(16)(17)(18). What has emerged from these studies is that loss of the lid does not interfere with interdomain coupling (15), and loss of the lid results in a 2-20-fold increase in K d values for peptide interaction with the ADPbound state of lidless DnaK (17,18).…”
mentioning
confidence: 99%